Pharmacokinetics in neonatal prescribing: evidence base, paradigms and the future. (26th October 2015) - O'Hara, Kate; Wright, Ian M. R.; Schneider, Jennifer J.; Jones, Alison L.; Martin, Jennifer H.
Abstract : Paediatric patients, particularly preterm neonates, present many pharmacological challenges. Due to the difficulty in conducting clinical trials in these populations dosing information is often extrapolated from adult populations. As the processes of absorption, distribution, metabolism and excretion of drugs change throughout growth and development extrapolation presents risk of over or underestimating the doses required. Information about the development these processes, particularly drug metabolism pathways, is still limited with weight based dose adjustment presenting the best method of estimating pharmacokinetic changes due to growth and development. New innovations in pharmacokinetic research, such as population pharmacokinetic modelling, present unique opportunities to conduct clinical trials in these populations improving the safety and effectiveness of the drugs used. More research is required into this area to ensure the best outcomes for our most vulnerable patients.